Formalization of the process of organization of the cargo delivery system - Коскіна, Юлія Олексіївна (Science-based technologies, 2020)
The implementation of a trade deal puts the seller and buyer in need to organize the transportation of the goods to a certain geographical point within the responsibility of each of them in accordance with the goods' delivery terms. To do this, they have to resort to the services companies that provide the movement of goods and/or propose a range of services related to the movement. The organization of goods delivery system is considered in the present paper as a choice of companies that implement the necessary range of transportation services at certain stage of the movement of goods, the responsibility of which lies on the seller and the buyer. A proposed mathematical model of the organization of the goods delivery system based on the terms of the purchase contract and the interests of its parties. Considering the natural desire of the seller and the buyer to reduce their transportation expenses, one of the most important criteria for choosing a company is the cost estimate of the services provided. The key interest of each of them is the movement of goods within the time interval of delivery of goods under the terms of purchase contract - for seller and the own interests regarding the arrival of the goods at the point of destination – for buyer. Accordingly, companies that should be involved in the delivery of goods, are to provide the services on the time that ensure the relevant interests of the parties. The value of transportation costs of each of the party by stage, that this party is responsible for, should be correlated: by the seller – with the difference with the prices for goods at the point of their production and the transfer of responsibility for subsequent transportation form seller to buyer; by the buyer – in the points of the origin his obligation for transportation and final destination. Transportation costs at the appropriate stages of goods movement should not only be minimized, they should ensure the economic feasibility of the concluding the purchase contract on a certain terms of the goods delivery. The proposed mathematical model can be used in the practical activity of the companies interested/in need in organizing the delivery of goods both for organizing the transportation of goods under the terms of already concluded contract and when planning the deal.